PREPARATION OF BIO-NEMATICIDAL NANOPARTICLES OF EUCALYPTUS OFFICINALIS FOR THE CONTROL OF CYST NEMATODE (HETERODERA SACCHARI) - Fabiyi; Oluwatoyin1; Olatunji; Gabriel; Atolani; Olubunmi; Olawuyi; Olanike (Journal of Animal and Plant Sciences, 2020)
The production of Oryza sativa (rice) which is one of the most important food crops is greatly limited by nematode infestations. While various integrated control measure which include the application of synthetic nematicidal agents have been adopted, success without some major setback has been elusive. Thus, the need for concerted worldwide intensive research for safer alternatives has become imperative. Silver nanoparticles (NPs) of Eucalyptus officinallis were prepared via green synthesis approach. The nanoparticles obtained were subjected to UV-Vis and FT-IR spectroscopies for the absorption and functional groups characterisations respectively. Surface Plasmon Resonance (SPR) was achieved at 451nm, indicating the formation of NPs and the FTIR showed functional groups which further confirmed the formation of nanoparticles. The NPs significantly (p=0.05) reduced nematode population in root and soil, increased vegetative growth of rice plant, with a significant corresponding increase in yield. The plant-based nematicidal agent of silver nanoparticles origin cheaply prepared in this study adds credence to claim that bio-nematicides holds promise as a cost-effective, efficient and eco-friendly option for the future.
Keywords: Cyst nematode; nanoparticles; Oryza sativa; Heterodera sacchari; environmental pollution; bio-nematicides